Edukasi Masyarakat Sekolah Melalui Pelatihan Kewirausahaan Sebagai Upaya Menumbuhkan Jiwa Kewirausahaan dan Menggali Ide Usaha - Annis Kandriasari; Ari Fadiati; Balqish Fatra Agniya; Fajar Firmansyach (Universitas 45 Surabaya, 2024)
The UNJ PPM Strategic Plan 2021-2025 is directed at 5 (five) focus activities, namely: (1) Education, (2) Poverty Alleviation, (3) Cultural Arts, (4) Environment, and (5) Creative Industries. Broadly speaking, the implementation of this PKM program is the empowerment of the school community in the preparation of PKM plans to provide education in the form of providing applied material regarding fostering an entrepreneurial spirit that can be applied in improving school businesses in the form of a canteen so that it can be an income generating school. Another goal is to explore business ideas by utilizing food ingredients that have the potential to be developed. This training is expected to provide knowledge and understanding of the training material, motivate and inspire trainees to utilize local food ingredients into various business ideas so as to create entrepreneurship in schools.